2015
DOI: 10.1016/j.braindev.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Improved prefrontal activity in AD/HD children treated with atomoxetine: A NIRS study

Abstract: These results suggest that long-term treatment with ATX improved prefrontal hemodynamic activity in AD/HD children, and NIRS may be useful for assessment of the prefrontal hemodynamic response to ATX treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…The CPT has been used to evaluate the effects of a pharmacological treatment on prefrontal activity in children with ADHD (Araki, et al, 2014). In an age-matched control group, children had increased oxygenated hemoglobin (oxy-Hb) concentration in the bilateral dorsolateral PFC (dlPFC).…”
Section: Measurements Of Rri In Humansmentioning
confidence: 99%
“…The CPT has been used to evaluate the effects of a pharmacological treatment on prefrontal activity in children with ADHD (Araki, et al, 2014). In an age-matched control group, children had increased oxygenated hemoglobin (oxy-Hb) concentration in the bilateral dorsolateral PFC (dlPFC).…”
Section: Measurements Of Rri In Humansmentioning
confidence: 99%
“…They found that ATX induced an intensified prefrontal hemodynamic response [31]. In another NIRS study, Araki et al found that the oxy-Hb concentration in the right dorsolateral PFC in the post-ATX condition was significantly increased compared to the pre-ATX condition during a continuous performance task [32]. Despite several NIRS studies with ADHD, only a few studies have examined the therapeutic effects of medication.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in brain activation levels using fNIRS have been found to differentiate known clinical groups from typically developing children (Ishii-Takahashi et al, 2014, Wiley et al, 2014) and to be related to parent-reported measures of behavioral functioning (Perlman et al, 2014). Changes in activation obtained from fNIRS have already been used to assess the impact of pharmacological interventions for children with Attention Deficit-Hyperactivity Disorder (ADHD) (Oner et al, 2011, Schecklmann et al, 2011, Monden et al, 2012, Matsuura et al, 2014, Araki et al, 2015) but have not yet been applied to understanding individual differences in children with FASDs.…”
Section: Introductionmentioning
confidence: 99%